2021
DOI: 10.1002/ajp.23231
|View full text |Cite|
|
Sign up to set email alerts
|

Color‐hierarchies in executive control of monkeys' behavior

Abstract: Processing advantages for particular colors (color-hierarchies) influence emotional regulation and cognitive functions in humans and manifest as an advantage of the red color, compared with the green color, in triggering response inhibition but not in response execution. It remains unknown how such color-hierarchies emerge in human cognition and whether they are the unique properties of human brain with advanced trichromatic vision. Dominant models propose that color-hierarchies are formed as experience-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(164 reference statements)
0
9
0
Order By: Relevance
“…There was also a slight advantage of terminating red flashes over other colors such as blue and green, as participants were more veridical in reporting their location as well. This small improvement in accuracy for red flashes in the terminating condition may arise from a stronger weight for red signals in stopping, as has been shown in studies investigating response inhibition (Blizzard et al, 2017;Ghasemian et al, 2021). The lack of significant differences between the other colors in the terminated condition may be due to the smaller magnitude of the perceptual shifts when the flash terminates the motion sequence.…”
Section: Discussionmentioning
confidence: 73%
“…There was also a slight advantage of terminating red flashes over other colors such as blue and green, as participants were more veridical in reporting their location as well. This small improvement in accuracy for red flashes in the terminating condition may arise from a stronger weight for red signals in stopping, as has been shown in studies investigating response inhibition (Blizzard et al, 2017;Ghasemian et al, 2021). The lack of significant differences between the other colors in the terminated condition may be due to the smaller magnitude of the perceptual shifts when the flash terminates the motion sequence.…”
Section: Discussionmentioning
confidence: 73%
“…There was also no relationship evident between response inhibition and driving experience. Ghasemian et al (2021) showed that the effects of red on response inhibition as measured in the stop‐signal task is dependent on inherent neural circuitry. Thus, if red's effect on response inhibition is inherent and not due to an association created through man‐made inventions in driving (e.g., traffic lights, brake lights) where red corresponds to stop, this could explain the lack of driving status modulating performance, independent to cue utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition ability (also known as response inhibition) is a key executive function which enables deliberate suppression of inappropriate actions, thoughts, and emotions. It has been examined by behavioral tools such as stop-signal paradigm (Ghasemian et al, 2021a;Mansouri et al, 2016Mansouri et al, , 2017aVerbruggen et al, 2019). In this paradigm, subjects deliver a speeded response in a primary task (Go trials), which is a simple or choice reaction time task, and withhold response in smaller proportion of trials (Stop trials).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, executive control is greatly dependent on prefrontal cortical regions (Aron et al, 2014;Mansouri et al, 2017bMansouri et al, , 2020aRoberts et al, 1998) which are different in terms of organization and cytoarchitecture between rodents and human (Petrides et al, 2012), whereas macaque monkeys are very closer to human in such respects (Mansouri et al, 2017b;Petrides et al, 2012;Roberts and Clarke, 2019). Moreover, a close homology exists between humans and macaque monkeys in the way that contextual factors affect their executive functions (Ghasemian et al, 2021a(Ghasemian et al, , 2021bMansouri et al, 2007Mansouri et al, , 2020aRoberts and Clarke, 2019). Therefore, macaque monkeys are suitable models for studying the time course of alterations in inhibition ability and providing more insights regarding the vulnerability of executive control in situations that resemble medical or recreational use of prescribed opioids in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation